2016
DOI: 10.1016/j.ecoleng.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and mitigation of denitrification ‘woodchip’ bioreactor phosphorus releases during treatment of aquaculture wastewater

Abstract: Denitrification 'woodchip' bioreactors designed to remove nitrate from agricultural waters may either be phosphorus sources or sinks. A 24 d batch test showed woodchip leaching is an important source of phosphorus during bioreactor start-up with a leaching potential of approximately 20-30 mg P per kg wood. The most rapid phosphorus release occurred within the first 24 h regardless of deionized water or aquaculture wastewater matrices; the Elovitch equation generally best modeled this multi-phasic P leaching. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…On average, there was a miniscule net removal of phosphorus at sites 2 and 3, and the capability of these wood-based bioreactors to remove smaller amounts of phosphates is consistent with previous woodchip bioreactor studies (e.g., Schipper et al, 2010a;Warneke et al, 2011;Sharrer et al, 2016). In contrast, a net production of dissolved phosphorus at site 1 was probably caused by the longer retention time and nitrate-limited conditions triggering other types of respiratory processes in the bioreactor.…”
Section: Organic Matter and Nutrient Leachingsupporting
confidence: 87%
See 1 more Smart Citation
“…On average, there was a miniscule net removal of phosphorus at sites 2 and 3, and the capability of these wood-based bioreactors to remove smaller amounts of phosphates is consistent with previous woodchip bioreactor studies (e.g., Schipper et al, 2010a;Warneke et al, 2011;Sharrer et al, 2016). In contrast, a net production of dissolved phosphorus at site 1 was probably caused by the longer retention time and nitrate-limited conditions triggering other types of respiratory processes in the bioreactor.…”
Section: Organic Matter and Nutrient Leachingsupporting
confidence: 87%
“…When observed, leaching of phosphorus does typically not last as long as leaching of organic matter, and the most rapid release seems to happen during the first 24 h (Sharrer et al, 2016;von Ahnen et al, 2016b).…”
Section: Organic Matter and Nutrient Leachingmentioning
confidence: 99%
“…Saliling et al (2007) also showed that woodchips are suitable as a reactor media but estimated that their expected life span was only up to 1 year. Later, a life span of over 10 years has been estimated for similar purposes (Sharrer et al 2016), while 5-15 years has also been reported due to slow degradation of woodchips under anoxic conditions (Schipper et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…High nitrate concentrations (> 100 mg L −1 NO 3 -N, Chen et al 2002) can be harmful for the raised species but also potentially lead to eutrophication of the receiving waters if released untreated. Eutrophication of water bodies is globally a severe problem (Sharrer et al 2016). It has been estimated that annual economic losses due to eutrophication is over 2.2 billion US dollars (Dodds et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus concentrations in both the Ridgely Farm bioreactor inflow and outflow were nearly always higher than concentrations known to impair freshwater (0.03 mg TP/L; Figure 4c,d) [26]. Flushing of phosphorous has been observed during start-up at other bioreactors [18,27], but concentrations as high as seen here are likely related to the farm characteristics (see above). Nevertheless, there was a statistically significant difference between bioreactor inflow and outflow phosphate concentrations, but no overall significant impact on total phosphorus concentrations when assessed over the entire monitoring period (Table 3; PO 4 p = 0.004; TP p = 0.097).…”
Section: Ridgely Farm Bioreactormentioning
confidence: 74%